Police in the nation state - an apolitical and independent institution? - Kołodziej, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Police is one of the most important institution related to security in nation state, which in the era of globalization is subject to constant changes. The police as institution was established to protect people`s safety and to maintain public safety and order. In order to be able to effectively carry out its tasks, the police must have social trust and be perceived as an independent and apolitical institution.
Keywords: police; dispositional group; social trust; apolitical institution